Factors Affecting Migration of Contaminants from Paper through Polymer Coating into Food Simulants. (7th September 2012) - Huang, Xiu‐Ling; Wang, Zhi‐Wei; Hu, Chang‐Ying; Zhu, Yong; Wang, Jun
Abstract : The migration of two surrogate contaminants, 1‐hydroxycyclohexyl‐1‐phenyl ketone (184) and benzyldimethyl ketal (651), from different paper into different food simulant (10% ethanol, 95% ethanol and isooctane) through different polymer coating low density polyethylene (LDPE) and polypropylene (PP) was studied. The paper samples were spiked with anhydrous ethanol solution containing the two surrogates and were dried using vacuum dry oven with vacuum degree 0.01 MPa and temperature 55°C and then subjected to migration experiments by using single‐sided contact method at 20°C. The concentration of surrogates in 10% ethanol, 95% ethanol and isooctane food simulants were determined by gas chromatography with flame ionization detector after predisposal. Effect factors on migration were discussed from different aspect such as food simulant, paper property, thickness of polymer coating and type of polymer coating. The results showed that the migration rate was faster in fatty food simulant 95% ethanol and isooctane than in aqueous food simulant 10% ethanol, a thicker LDPE coating delayed the migration process of contaminant, paper with lower density and higher porosity would increase migration speed and the barrier property of PP was far away higher than that of LDPE, even if the thickness of LDPE was thicker a lot than PP. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : The migration of two surrogate contaminants, from different paper into different food simulant through different polymer was studied. Effect factors on migration were discussed from different aspect such as food simulant, paper property, thickness of polymer coating, type of polymer coating. The results showed that the migration rate was faster in fatty food simulant than in aqueous food simulant, a thicker LDPE coating delayed the migration, paper with lower density and higher porosity would increase migration speed and the barrier property of PP was far away higher than that of LDPE, even if the thickness of LDPE was thicker a lot than PP.